Food Safety Practice and Associated Factors of Food Handlers Working in Food Industries in Bahir Dar City, Amhara Regional State, Northwest Ethiopia, 2021 - Mekuriaw Alemu; Achenef Motbianor; Dereje Birhanu; Amsalu Birara (SAGE Publishing, 2023)
Background: Food safety has emerged as one of the 10 threats to global health. Ethiopia is among the developing countries with many food industries in recent times. Poor food handling procedures, a lack of basic infrastructure, lack of potable water, lack of financial resources to invest in safer equipment, and lack of training for food handlers have all been reported. Objectives: To assess food safety practices and associated factors among food handlers working in food industries in Bahir Dar city administrations. Methods: A cross-sectional study was conducted from January to February 2021 among 422 food handlers working in food industries in Bahir Dar city, Ethiopia. A random sampling technique was used to select food industries and study participants. The sample size was proportionately allocated to the selected food industries. Data were collected through face-to-face interviews and observation methods using interviewer-administered questionnaires and an observational checklist respectively. Data was entered into Epi-data v 3.1 and exported to SPSS v 23 for analysis. Bi-variable binary logistic regression was carried out to identify candidate variables at p -value <.2 and was entered into the final multivariable binary logistic regression model to control the effect of confounding. Variables with p -values of less than .05 were declared as statistically significant and an odds ratio of 95% CI was used to measure the strength of the association. Result: Food safety practice among food handlers working in food industries was 47.6% (95% CI: 42.8, 52.5). Sex [AOR: 2.92 (CI: 1.77, 4.82)], monthly salary [AOR: 2.02 (CI: 1.18, 3.44)], health supervision [AOR: 3.43 (CI: 1.97, 5.97)], working unit [AOR: 2.44, (CI: 1.45, 4.13], food safety training [AOR: 6.16 (2.97, 12.77)], attitude [AOR: 3.55 (CI: 1.14, 11.05)] were factors significantly associated with food safety practice. Conclusion: Food safety practice among food handlers was low. Sex, working unit, monthly income, regulatory supervision, food safety training, and attitude toward food safety were factors associated with poor food safety practices. In-service training on good hygiene practices, good manufacturing practices, hazard analysis, critical control point, food safety management systems, and supportive supervision should be strengthened.